(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
The purpose of the trial was to determine whether combination medication for type 2 diabetes mellitus offers better glycemic control than monotherapy. Subjects whose ages were more than 18 years and with glycated hemoglobin levels higher than 7.5% were enrolled. Among the 664 patients enrolled, 332 received monotherapy, while 332 were treated with combination therapy. The treatment groups received either vildagliptin + metformin combination therapy or metformin monotherapy. Vildagliptin, as an adjunct to metformin treatment, was to be evaluated for its safety and efficacy in reducing HbA1c levels from baseline. The study included individuals with a history of T2DM for 3 to 4 years who had been treated with either combination therapy or monotherapy for at least three months. Statistical analysis was done using SPSS software. As per the findings, it indicated that combination therapy led to a considerably greater reduction in glycated hemoglobin levels compared to monotherapy. Adverse events were also observed to vary significantly between the two treatment cohorts. Outcomes suggest that combination medication should be started earlier than monotherapy for superior glycemic control. Additionally, it was thought that the combo therapy had a positive safety profile.